2018
DOI: 10.1177/0266242618782596
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and business performance for Spanish SMEs: New evidence from a multi-dimensional approach

Abstract: This article examines the impact of product, process and organisational innovations on two alternative dimensions of business performance: finance and operations. Two indicators capture financial performance: sales increase and production cost reduction. Operational firm performance is captured by two alternative indicators: productive capacity augmentation and quality improvement of product/service provided by the firm. Using a wide-ranging sample of Spanish small- and medium-sized enterprises (SMEs), our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 81 publications
(153 reference statements)
7
73
0
9
Order By: Relevance
“…The survey was addressed to the person holding the role of the entrepreneur in the firm, defined as "the person who performs principal managerial functions within the business." (Exposito and Sanchis-Llopis 2018). In this regard, several studies have demonstrated empirical evidence that SME managers implement "the most important decisions within their organizations" (Van Gils 2005; Exposito and Sanchis-Llopis 2018), including those regarding innovation strategies and their managerial perceptions shape the firm's strategic behaviour to an essential degree Donate and Pablo 2015).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey was addressed to the person holding the role of the entrepreneur in the firm, defined as "the person who performs principal managerial functions within the business." (Exposito and Sanchis-Llopis 2018). In this regard, several studies have demonstrated empirical evidence that SME managers implement "the most important decisions within their organizations" (Van Gils 2005; Exposito and Sanchis-Llopis 2018), including those regarding innovation strategies and their managerial perceptions shape the firm's strategic behaviour to an essential degree Donate and Pablo 2015).…”
Section: Data Collectionmentioning
confidence: 99%
“…In this regard, several studies have demonstrated empirical evidence that SME managers implement "the most important decisions within their organizations" (Van Gils 2005; Exposito and Sanchis-Llopis 2018), including those regarding innovation strategies and their managerial perceptions shape the firm's strategic behaviour to an essential degree Donate and Pablo 2015). Furthermore, several other studies suppose that self-reported information by managers can be used as an appropriate approach to measure business strategy variables including innovation and business performance (Foreman-Peck 2013; Goya et al 2016;Madrid-Guijarro et al 2013;Ramadani et al 2017;Ribau et al 2017;Exposito and Sanchis-Llopis 2018;Wang and Ahmed 2004) and financial slacks (Parida and Örtqvist 2015;Boso et al 2017).…”
Section: Data Collectionmentioning
confidence: 99%
“…[1][2][3] In this scenario, innovation has been acknowledged as an influential impelling cause for the survival, success and competitiveness of high-tech organizations. [4][5][6][7][8][9] However, it has become challenging for business leaders to encourage their members to leave the traditional way of thinking and task performance, and to devote their energy to creating innovative ideas. 10 Innovation comes out when the employees working at all levels of organizational hierarchical structure show innovative work behavior, and devote their efforts to developing, promoting and implementing new ideas in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…While a person can be a leader, he may not be a manager. (Esposito and Sanchis-Llopis, 2018) At this point in time, it is essential to explain that the term leadership and manager are not synonymous. (Moron, 2004) "The term leader and manager are not necessarily interchangeable because leadership is a subclass of management.…”
Section: Introductionmentioning
confidence: 99%